Sexual Harassment and Violence in the Practice of Anthropology: Creating Safe Conversational Spaces for CASCA Members - Sax, Marieka; Grenon, Marie; Manzano-Munguía, María; Joly, Tara (Anthropologica)

(untitled) (University of Victoria, 2022)
The Canadian Anthropology Society is working to address sexual harassment and violence at institutional and community-based settings where anthropologists undertake their work. In 2021, the newly formed Sexual Harassment and Violence Working Group held a roundtable at the CASCA conference to start a conversation about sexual violence among CASCA members and to workshop best practices to prevent, disrupt, and respond to incidents of sexual harassment and violence that CASCA members may experience or observe. Here, the Working Group summarizes the process of planning, implementing, and following up the roundtable, focusing on specific actions taken by the organizers to ensure a safe conversational space before, during, and after the event. We demonstrate how the roundtable aligns within the larger framework of CASCA’s institutional history and future. The goal of this report is to provide a framework for convening difficult conversations in professional settings, especially in an online environment. We provide recommendations to this end, and emphasize the need to hold further conversations to combat the air of silence that remains, even in a post-#MeToo world, surrounding sexual violence in anthropology.